6,000 miles to freedom : two boys and their flight from the Taliban - Marchetti, Stéphane, 1978- (Graphic Mundi, 2022)
"A narrative account, in graphic novel format, of the traumatic experiences faced by children fleeing war and poverty in Afghanistan, as well as the isolation they often feel as refugees in the West"--